Metode peningkatan keterampilan anak tuna netra mengaduk ransum ternak ayam petelur di SLB Tuna Netra Payakumbuh - Yarmis Hasan; Armaini Armaini; Mindawati Mindawati; Irdamurni Irdamurni (Jurnal Abmas, 2002)
The blind children are hoped that they could solve their own life. They are prepared in order to be capable and live without any awkwardness in society, and also for helping the Social Department and all at once to face the changing of area autonomy. Along with the aim itself, so this training is given to the blind children including the teachers. One of the skills is in mixing the ration of chicken egg layer, so they are able to take care of it by concerning the composition of the chicken's food and appropriate with the needs. Strategy that is used is facing strategy, by visiting the object to be given an education and job training whether in the room or in the field. So, the method that is used is speech method as discussion and interview, and the method that is given to the blind children is especially in orientation and mobility. From this dedication activity can be summarized that by using the orientation and mobility method, the blind children could do the mixing of the ration of chicken egg layer.